Convento do Bom Sucesso (1639 – 2016): um caso de continuidade histórica - Rodrigues, Sofia Ferreira (Lusitania sacra, 2024)
The history of Bom Sucesso is linked to the history of the city of Lisbon, and the history of Portugal more broadly. It is important to note that the Convent remained in the same location during the extinction of the religious orders in Portugal, arguably because it was Irish and the nuns promised to open a school on the site. The foreign nature of the congregation became firmly established during the Portuguese First Republic, (1910-1926), when it was decided that Portuguese postulants, and later nuns, would not be admitted to the convent. During its early years, from 1630 to the end of the 17th century, the convent and religious community around it established their defining characteristics. These have been gradually consolidated during the time that the Convent has existed. The "sisters", as they have always been known, lived in the convent from 1639 up until 2016, except for an absence of a month in 1823. In 2016, they returned to their home county of Ireland having remained leaders of the Foundation known as Fundação Obra Social das Religiosas Dominicanas Irlandesas (Irish Dominican Foundation for Social and Religious Work). This article will focus on the spiritual and architectural aspects of the Convent that have been in place since its foundation and throughout its existence.